2017
DOI: 10.1140/epjc/s10052-017-4923-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of $$f(R,T,R_{\mu \nu }T^{\mu \nu })$$ f ( R , T , R μ ν T μ ν ) model on the stability of cylindrical stellar model

Abstract: The aim of this paper is to investigate the stable/unstable regimes of the non-static anisotropic filamentary stellar models in the framework of f (R, T, R μν T μν ) gravity. We construct the field equations and conservation laws in the perspective of this model of gravity. The perturbation scheme is applied to the analysis of the behavior of a particular f (R, T, R μν T μν ) cosmological model on the evolution of cylindrical system. The role of the adiabatic index is also checked in the formulations of the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…where total mass of the corresponding object is denoted by M(ν). We have found Darmois junction conditions and smooth matching criterion of the exterior and interior manifolds over the boundary for f (R, T, Q) gravity, which is provided by Yousaf et al [28] (after following Senovilla [56]). We establish some constraints at boundary surface r = r Σ as…”
Section: Field Equations Inmentioning
confidence: 64%
See 1 more Smart Citation
“…where total mass of the corresponding object is denoted by M(ν). We have found Darmois junction conditions and smooth matching criterion of the exterior and interior manifolds over the boundary for f (R, T, Q) gravity, which is provided by Yousaf et al [28] (after following Senovilla [56]). We establish some constraints at boundary surface r = r Σ as…”
Section: Field Equations Inmentioning
confidence: 64%
“…They also discussed the stability of some particular models in f (R, T, Q) theory by obtaining their solution through numerical techniques. Yousaf et al [26][27][28][29] studied the gravitational collapse in self-gravitating structures and calculated their equations of motion in f (R, T, Q) theory as well as some relations with Weyl tensor. Bhatti et al [30,31] studied the gravitational collapse in f (R, T, Q) theory and calculated few constraints under which the systems would enter into the collapsing phase.…”
Section: Introductionmentioning
confidence: 99%
“…where M is a gravitating mass of the corresponding object. For the smooth matching of outer and inner manifold across the boundary, we consider Darmois junction conditions and matching criterion provided by Yousaf et al [26] (after following Senovilla [48]) for f (R, T, Q) gravity. At boundary surface r = r Σ =, we found that…”
Section: Modified Field Equationsmentioning
confidence: 99%
“…They found numerical solution of some special models of f (R, T, Q) theory to discuss their stability. In the gravitational collapse of spherical structure, Bhatti et al and his collaborators [25][26][27][28] analyzed the role of the physical variables on the dynamical evolution of self-gravitating systems and found the relation of structural variables with that of Weyl tensor in f (R, T, Q) theory.…”
Section: Introductionmentioning
confidence: 99%
“…ey [33] analyzed the role of electric charge on the entire analytical solutions which are stable, nonevent horizon and singularity free in nature. Also, Yousaf and his collaborators [34][35][36][37][38] have worked on the stability of gravastars in several modified theories of gravity.…”
Section: Introductionmentioning
confidence: 99%